Influencia de la motivación en la gestión de equipos de trabajo en la empresa Cisesa Comunicaciones S.A.C sucursal Chepén, año 2015 - Mostacero Quiroz, María Rosa (2017)
This research has as its main objective to know the influence of motivation in managing teams in the company Cisesa Communications Branch S.A.C Chepén, Year 2015, where the next problem arises: How motivation influences the management teams of the company Cisesa Communications Branch S.A.C Chepén, Year 2015?, so the following hypothesis was proposed: "the motivation has a positive influence on the management teams in the business Cisesa Communications Branch S.A.C Chepén, Year 2015” The research methodology used was Type: Applied, not experimental and descriptive, inductive-deductive method, hypothetical-deductive method and Analysis-Synthesis Method with a descriptive design was used - Transversal, the survey was also used as a technique investigation. According to the results, I can say that there is a direct relationship between motivation and management teams, because if there is a better perception management will be greater worker commitment to the company. By the results presented in this research, the company can prepare contingency plans to encourage employees to motivate them, that part of the working team sitting and implement management strategy that encourages the worker to commit each day with the company.